Correlates of Cervical Cancer Screening Among Adult Latino Women: A 5‐Year Follow‐Up. Issue 2 (June 2017) - Rojas, Patria; Li, Tan; Ravelo, Gira J.; Dawson, Christyl; Sanchez, Mariana; Sneij, Alicia; Wang, Weize; Kanamori, Mariano; Cyrus, Elena; De La Rosa, Mario R.
Abstract : Background: Latinas have the highest incidence rates of cervical cancer in the United States, and Latinas in the United States are less likely to utilize cervical cancer screening. We used secondary data analysis of a nonclinical convenience sample ( n  = 316 women at baseline; n  = 285 at 5‐year follow‐up) to examine correlates of cervical cancer screening among adult Latina women. Univariate and multiple logistic regression models using generalized estimated equations (GEE) algorithm were utilized to assess the influence of the independent variables. Women who reported their main health‐care source as community health clinics, women who were sexually active, and women who reported that a health‐care provider discussed HIV prevention with them were more likely to report having had a cervical cancer screening (aOR = 2.06; CI = 1.20, 3.52). The results suggest a need for continued efforts to ensure that medically underserved women (e.g., Latina women) receive counseling and education about the importance of preventive cervical cancer screening.